Update on the diagnosis and treatment of the principal primary headaches in the child (Revista de Medicina Clinica, 2017)
Primary headaches, especially migraine and tensional headache are both, a public health issue in children.Due to their prevalence of 1 to 11% in children and 8 to 23% in adolescents in both genders. Considered the first causeof health care consultation, they are a very important cause of school absenteeism and a decrease in the quality of life ofchildren. The objective of this non-systematic review is the analysis of the pathophysiological bases, classification andred flags that support for the differential diagnosis between primary and secondary headaches; Aside from performing anupdate on the pharmacological and non-pharmacological treatment of the main school-age primary headaches, migraineand tension headache. Rev Med Clin 2017;1:1-14.
Keywords: primary headache; tensional headache; migraine; child